Oblique lateral interbody fusion stand-alone vs. combined with percutaneous pedicle screw fixation in the treatment of discogenic low back pain - Wang, Weiheng; Xiao, Bing; Wang, Haotian; Qi, Junqiang; Gu, Xin; Yu, Jiangming; Ye, Xiaojian; Xu, Guohua; Xi, Yanhai (Frontiers in Surgery, 2022)
Objective Oblique lateral interbody fusion (OLIF) has unique advantages in the treatment of discogenic low back pain (DBP). However, there are few studies in this area, and no established standard for additional posterior internal fixation. The purpose of this study was to investigate the efficacy of OLIF stand-alone vs. combined with percutaneous pedicle screw fixation (PPSF) in the treatment of DBP. Methods This retrospective case-control study included forty patients. All patients were diagnosed with DBP by discography and discoblock. Perioperative parameters (surgery duration, blood loss, and muscle damage), complications, Visual analog scale (VAS), and Oswestry Disability Index (ODI) were assessed. Imaging data including cage subsidence, cage retropulsion, fusion rate, and adjacent spondylosis degeneration (ASD) were analyzed. Results There were 23 patients in the OLIF stand-alone group and 17 patients in the OLIF + PPSF group. The mean surgery duration, blood loss, and muscle damage in the OLIF stand-alone group were significantly better than those in the OLIF + PPSF group (P < 0.05). However, there was no significant difference in the average hospitalization time between the two groups (P > 0.05). There was no significant difference in the VAS and ODI scores between the two groups before surgery (P > 0.05), and VAS and ODI scores significantly improved after surgery (P < 0.05). The VAS and ODI scores in the OLIF stand-alone group were significantly better than those in the OLIF + PPSF group at 1 month (P < 0.05), While there was no significant difference between the two groups at 12 months and last follow up (P > 0.05). At the last follow-up, there was no significant difference in cage subsidence, fusion rate, ASD and complication rate between the two groups (P > 0.05). Conclusion OLIF stand-alone and OLIF + PPSF are both safe and effective in the treatment of DBP, and there is no significant difference in the long-term clinical and radiological outcomes. OLIF stand-alone has the advantages of surgery duration, blood loss, muscle damage, and early clinical effect. More clinical data are needed to confirm the effect of OLIF stand-alone on cage subsidence and ASD. This study provides a basis for the clinical application of standard DBP treatment with OLIF.